The use of echocardiography in certified chest pain units: results from the German Chest Pain Unit Registry - Breuckmann, Frank; Giannitsis, Evangelos; Schumacher, Burghard (Cardiology, 2016)
Objectives: To analyze the current usage of transthoracic echocardiography (TTE) as a rapid, noninvasive tool in the early stratification of acute chest pain in certified German chest pain units (CPUs). Methods: A total of 23,997 patients were enrolled. Analyses comprised TTE evaluation rates in relation to clinical presentation, risk profile, left ventricular impairment, final diagnosis and invasive management. Critical times were assessed. Multivariable analyses for independent determinants for the use of TTE were performed. Results: TTE evaluation was available in CPUs in 70.1% of cases. It was associated with lower rates of invasive management in unstable angina pectoris (UAP) and with higher rates in patients with initially suspected non-cardiac origin of symptoms and/or reduced systolic function (p < 0.05). Non-ST-segment elevation acute coronary syndrome (NSTE-ACS) was an independent determinant favoring TTE evaluation [NSTE-myocardial infarction: odds ratio (OR) 1.62; UAP: OR 1.34; p < 0.001 for both]. Clinical signs of heart failure (OR 1.31; p < 0.001), referral by emergency medical service (OR 1.18; p < 0.001) and kidney failure (OR 1.16; p < 0.05) were independently associated with higher TTE rates. TTE did not delay door-to-balloon times. Conclusions: About two thirds of the patients admitted to certified CPUs received TTE evaluation, with the highest rates being in ACS patients, and thereby providing diagnostic information supporting or refuting further invasive management.
Gesehen am 17.10.2019